2002
DOI: 10.1002/1521-4095(20021002)14:19<1399::aid-adma1399>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Designed Self-Doped Titanium Oxide Thin Films for Efficient Visible-Light Photocatalysis

Abstract: Efficient photocatalytic activity in the visible range has been achieved with titanium oxide thin films. Doping, induced by oxygen deficiencies, is the key to the increased photodegradation properties of the film as both experimental and theoretical studies of the thin films demonstrate. The Figure shows an AFM image of the surface morphology of a TiO2 layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
280
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(308 citation statements)
references
References 7 publications
20
280
0
3
Order By: Relevance
“…4(b). Other studies made similar conclusions that visible light activity of N-doped TiO 2 was ascribed to V O which induced donor states located below the CB, while substitutional N acted as an inhibitor for e --h + recombination (Justicia et al, 2002;Ihara et al, 2004). This controversy makes it necessary to decouple the contributions of V O and N-doping in TiO 2 in future studies.…”
Section: Electron Transfer From the Impurity State To Tio 2 Cbmentioning
confidence: 99%
“…4(b). Other studies made similar conclusions that visible light activity of N-doped TiO 2 was ascribed to V O which induced donor states located below the CB, while substitutional N acted as an inhibitor for e --h + recombination (Justicia et al, 2002;Ihara et al, 2004). This controversy makes it necessary to decouple the contributions of V O and N-doping in TiO 2 in future studies.…”
Section: Electron Transfer From the Impurity State To Tio 2 Cbmentioning
confidence: 99%
“…Their effects on the properties of the doped samples have been reported. Some research groups attempted to modify TiO 2 such that it showed response to visible wavelength through the use of oxygen-vacant TiO 2 [12], nonmetal-doped TiO 2 [13,14], and metal-nonmetal codoped TiO 2 [15] particles that have significant photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, doped TiO 2 materials are usually not adequate catalysts for photocatalytic hydrogen production from water splitting, although their superior activity in photocatalytic oxidation reactions have been well documented 6,18 . Self-doping with Ti 3 þ was further developed for narrowing the band of TiO 2 without the introduction of unwanted carrier recombination centres from dopants [19][20][21] , which consequently exhibited good stability and considerable activity for photocatalytic hydrogen production under visible light 20,21 . Recently, hydrogenation of crystalline TiO 2 was disclosed as a new approach to enhance the visible as well as infrared light absorption of pristine TiO 2 and subsequently triggered great interest [22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%